An Analysis of Independence in Children and Adolescents with Intellectual Disabilities at MILB YKTM Budi Asih - Fitriani, Dela Ayu; Putri, Nisrina Nurviani; Setiawan, Mohamad Dwiki; Fa`idah, Pramatika Nurul; Masfia, Irma; Fahmy, Zulfa (Lembaga KITA, 2024)
Independence refers to an individual's ability to carry out daily activities without relying on others, such as self-care, interacting with the surrounding environment, and completing tasks autonomously. It also encompasses emotional, behavioral, moral, and intellectual aspects that enable a person to navigate daily life without dependence on others. This study aims to analyze the level of independence among children and adolescents with intellectual disabilities at MILB YKTM Budi Asih. The research employed a descriptive qualitative method, collecting data through observations and interviews with students with intellectual disabilities, their parents, and teachers. The findings indicate that the level of independence among children and adolescents with intellectual disabilities at MILB YKTM Budi Asih varies across emotional, behavioral, moral, and intellectual aspects. Although there remains some dependence on parents for certain daily activities, the specialized education provided by the school has made efforts to support the development of independence among these children and adolescents.